2023
DOI: 10.1002/adma.202210378
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Self‐Assembling Nanofibrous Multidomain Peptide Hydrogels

Abstract: has been to chemically modify naturallyderived hydrogel materials to make them more printable, while attempting to maintain their favorable biological properties. Recently, two generalizable strategies have been proposed to allow for the printing of a wide range of hydrogel materials, which both include a stabilization method to allow for short term print fidelity, followed by a crosslinking method to impart longterm stability. [36,37] Despite these advances, naturally derived materials suffer from batch to ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 79 publications
0
29
0
Order By: Relevance
“…35b and c) that were used for cell culture, including creating tumour spheroids (Section 4.7). Recently, Hartgerink and co-workers extrusion-printed peptide hydrogels, 274 with applications in regenerative medicine (Section 4.7).…”
Section: Emergence Of Supramolecular Conceptsmentioning
confidence: 99%
“…35b and c) that were used for cell culture, including creating tumour spheroids (Section 4.7). Recently, Hartgerink and co-workers extrusion-printed peptide hydrogels, 274 with applications in regenerative medicine (Section 4.7).…”
Section: Emergence Of Supramolecular Conceptsmentioning
confidence: 99%
“…Based on a very similar principle, Hartgerink et al reported a nanofibrous hydrogel comprised of multidomain peptides with good viscoelastic properties for DIW. 178 The 3D-printed peptide hydrogels demonstrated their bio-computability for cell culturing.…”
Section: Supramolecularly Designed Diw Inksmentioning
confidence: 99%
“…Bioactive peptides can bind noncovalently to produce a diversity of supramolecular assemblages including nanoparticles and nanofibers, thus enhancing in vivo stability and bioavailability. Based on these characters, a large number of supramolecular assemblages have been extensively designed to form hydrogel and integrate with nanoarchitectures for extending bioapplication. For instance, a self-assembled chelating peptide hydrogel (PPH) was engineered to load with an osteogenic metal ion cluster extracted from the processed pyritum decoction . Since this PPH could regulate a variety of genes related to extracellular matrix synthesis, cell adhesion and migration, and cytokine expression in the process of bone regeneration, PPH would accelerate the progress of various bone healing stages and shorten the bone healing cycle.…”
Section: Classification Of Hydrogelmentioning
confidence: 99%